Pengaruh Media Audio Visual (Video) dalam Pendidikan Kesehatan terhadap Tingkat Pengetahuan Hipertensi di Desa Cikeusik Kecamatan Wanasalam - Rangga Saputra; Putri Andini; M. Martono Diel (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is one of the leading non-communicable diseases and a major cause of death worldwide. It is often referred to as the silent killer because it rarely shows specific symptoms, leaving many individuals unaware of their condition until serious complications occur. The low level of public knowledge about hypertension is a significant risk factor that contributes to poor prevention and control. Therefore, innovative health education strategies are urgently needed to improve community awareness, one of which is through audio-visual media such as video. This study aimed to determine the effect of audio-visual media (video) in health education on the level of knowledge about hypertension among residents of Cikeusik Village, Wanasalam Subdistrict. The research design applied was quantitative with a quasi-experimental method using a pretest-posttest with control group design. A total of 40 respondents were selected using a purposive sampling technique and divided into two groups: intervention (RT.005) and control (RT.004). The instrument used was a structured hypertension knowledge questionnaire. Data were analyzed using the Paired Sample T-Test to compare knowledge before and after the intervention, and the Independent Sample T-Test to compare differences between the intervention and control groups. The results indicated a significant improvement in hypertension knowledge after providing health education through audio-visual media (video) in the intervention group. The Independent Sample T-Test showed a significance value of p = 0.000 (p < 0.05), confirming that the use of audio-visual media had a positive and significant effect on respondents’ knowledge levels. Conclusion: audio-visual media (video) is proven to be an effective educational tool for improving community knowledge about hypertension and can be recommended as an attractive and easy-to-understand health promotion medium.